2022
DOI: 10.1002/pc.26967
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and shear behavior of plain weave fabric carbon fiber reinforced polymer at elevated temperatures

Abstract: Plain weave fabric carbon fiber reinforced polymer (CFRP) Composites are tested at four different temperature conditions: room temperature, 82 C, 100 C, and 120 C. The variation in their tensile and in-shear properties are studied. The tensile properties seemingly increased when the specimens are tested close to their curing temperature but reduced up to 7.88% with respect to the room temperature conditions, when they are tested close to their glass transition temperature. The in-plane shear strength and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…More details about the resin, fibre and prepreg are presented in Table 1. Further details about the preparation of composites can be found in the authors' previous research works [12]. From the cured CFRP slabs, tensile test specimens are cut according to ASTM D3039 standard longitudinally along the fibre warp direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More details about the resin, fibre and prepreg are presented in Table 1. Further details about the preparation of composites can be found in the authors' previous research works [12]. From the cured CFRP slabs, tensile test specimens are cut according to ASTM D3039 standard longitudinally along the fibre warp direction.…”
Section: Methodsmentioning
confidence: 99%
“…One, to assess the mechanical behaviour the composites using AE technique and two, to validate the efficacy of LZ complexity as an efficient AE parameter for the damage classification using deep learning neural networks. Readers, who are interested in the mechanical properties of the plain weave fabric CFRP such as the tensile strength, strain at failure and Young's modulus are directed to the authors' previous works [12]. To alleviate the confusion in differentiating fibre breaking and through-thickness crack growth, several researchers recommended the utilization of the frequency characteristics of the signal, say peak frequency [14,15].…”
Section: Deep Learning Neural Networkmentioning
confidence: 99%
“…Further, moisture, [61] temperature and loading speed [62][63][64][65][66][67][68] also have an influence. [27,69,70] The glass transition temperature (T g ) of the thermoset polymer matrices ideally used in FRP composites is a limiting factor that restricts their usage in high temperature environments. [71] The main focus of this work is to assess the elevated temperature delamination behavior (mode I and mode II ILFT) of carbon fiber/glass fiber epoxy interply epoxy hybrid composites.…”
Section: Introductionmentioning
confidence: 99%
“…So that the textile reinforced polymer composite has been widely studied and applied in a variety of areas due to its excellent performance. [16][17][18] As for textile reinforced concrete, its mechanical properties can also be effectively improved by pre-impregnation of textile with polymer. Some studies have showed that the impregnation on the textile decreases the empty spaces among filaments and improves the stress transfer, which increases not only the bonding but also the mechanical properties of TRC.…”
Section: Introductionmentioning
confidence: 99%